Associations of maternal and foetoplacental factors with prehypertension/hypertension in early childhood. Issue 11 (22nd November 2022) - Michael, Navin; Sadananthan, Suresh Anand; Yuan, Wen Lun; Ong, Yi Ying; Loy, See Ling; Huang, Jonathan Y.; Tint, Mya-Thway; Padmapriya, Natarajan; Choo, Jonathan; Ling, Lieng Hsi; Kramer, Michael S.; Godfrey, Keith M.; et al.
Abstract : Objective: To evaluate whether characterization of maternal and foetoplacental factors beyond birthweight can enable early identification of children at risk of developing prehypertension/hypertension. Methods: We recruited 693 mother–offspring dyads from the GUSTO prospective mother–offspring cohort. Prehypertension/hypertension at age 6 years was identified using the simplified paediatric threshold of 110/70 mmHg. We evaluated the associations of pregnancy complications (gestational diabetes, excessive/inadequate gestational weight gain, hypertensive disorders of pregnancy), foetal growth deceleration (decline in foetal abdominal circumference at least 0.67 standard deviations between second and third trimesters), high foetoplacental vascular resistance (third trimester umbilical artery systolic-to-diastolic ratio ≥90th centile), preterm birth, small-for-gestational age and neonatal kidney volumes with risk of prehypertension/hypertension at age 6 years, after adjusting for sex, ethnicity, maternal education and prepregnancy BMI. Results: Pregnancy complications, small-for-gestational age, preterm birth, and low neonatal kidney volume were not associated with an increased risk of prehypertension/hypertension at age 6 years. In contrast, foetal growth deceleration was associated with a 72% higher risk [risk ratio (RR) = 1.72, 95% confidence interval (CI) 1.18–2.52]. High foetoplacental vascular resistance was associated with a 58% higher risk (RR = 1.58, 95% CI 0.96–2.62). Having both these characteristics, relative to having neither, was associated with over two-fold higher risk (RR = 2.55, 95% CI 1.26–5.16). Over 85% of the foetuses with either of these characteristics were born appropriate or large for gestational age. Conclusion: Foetal growth deceleration and high foetoplacental vascular resistance may be helpful in prioritizing high-risk children for regular blood pressure monitoring and preventive interventions, across the birthweight spectrum.